Réponses

2014-02-07T12:57:57+01:00
5-(x-3)=4x-(3x-8)
5-x+3=4x-3x+8
-5-4x+3x=8-5-3
-2x=0
x=0

2+x-(5+2x)-7=3x+7
2+x-5-2x-7=3x+7
x-2x-3x=7+7+5-2
-4x=17
x= - 17/4

7(x+4)-3(x+2)=x+7
7x+28-3x-6=x+7
7x-3x-x=7-28+6
3x=-15
x= - 15/3
x= -5

2014-02-07T13:11:25+01:00
5-(x-3) = 4x - (3x-8)         1) suppression des parenthèses
5 -x +3 = 4x -3x +8)          2) tu passes les x devant le signe = en n'oubliant pas de 
-x -4x +3x = -5 -3 +8            changer les signes
-2x = 0
x = 0

2 +x - ( 5+2x) -7 = 3x +7
2 +x -5 -2x -7 = 3x +7
+x -2x -3x = -2 +5 +7 +7
-4x = +17
x = -17/4

7(x+4) -3 (x+2) = x +7
7x +28 -3x -6 = x + 7
7x -3x -x = -28 +6 +7
3x = -15
x = -15/3
x = -5